Efficient Strategies for Elimination of Phenolic Compounds During DNA Extraction from Roots of Pistacia vera L. - Saeideh Rajaei; Rana Sabagh Farshi; Maryam Moazzam Jazi; Seyed Mahdi Seyedi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Optimization of DNA extraction protocols for plant tissues and including endophytic microorganisms is a critical step of advanced plant-microbe interaction in agricultural studies. Pistachio (Pistacia vera L.) root tissue contains high levels of polyphenols have been known as major extract contaminants and inhibitors of enzymatic activities during amplification. The present study aimed to develop reliable strategies to purify DNA from Pistachio root samples. Inhibiting substances were removed from DNA through a process including extraction with hot detergent contains SDS-Tris- EDTA, AlNH4(SO4)2.12H2O as chemical coagulating factor and CTAB-NaCl. Following typically organic extraction/alcohol precipitation, denaturing agarose electrophoresis performed to purify probable remain contaminants. The purified DNA was enough free of polyphenols based upon loss of color and spectral quality (260/230>1.6) and efficiently amplified during polymerase chain reaction particularly in the present of GC-clamp primers. This method proved well with detection of Glomus sp. (arbuscular mycorrhiza fungi) associated with Pistacia vera L. using denaturing gradient gel electrophoresis (DGGE).